National audits of hip fractures: Are yearly audits required?. Issue 2 (February 2016) - Ferguson, Kim B.; Halai, Mansur; Winter, Alison; Elswood, Tom; Smith, Rik; Hutchison, James D.; Holt, Graeme
Abstract: Introduction: Hip fractures are a significant cause of morbidity and mortality to the increasing elderly population. The Scottish Hip Fracture Audit started in 1993 with national audits from 2002. It was a national prospective audit reporting on clinical standards in hip fracture care and produced an annual report. Due to national funding changes the continual audit was discontinued in 2008. In 2013, the MSK Audit Group published a "snapshot" into a 4 month period of hip fracture care in Scotland. Our purpose was to identify whether there had been an initial improvement in hip fracture care and whether this improvement was sustained with the discontinuation of the annual audit. Methods: The reported outcomes from the annual Scottish Hip Fracture Audit from 2003 to 2008 were compared to the latest MSK Hip Fracture Audit published in 2013. Some data is available from the 2014 MSK Hip Fracture Audit and this was also used for comparison purposes. Local audit co-ordinators at each participating site collected a data-set for all patients admitted with a hip fracture. The case mix variables and management variables were compared for the reported years. Results: The continual audit demonstrated an improvement in the percentage of patients discharged from accident and emergency in 4 h (80.5% 2003 vs. 96% 2008) which was not maintained 5 years later. An improvement in the percentage of patients having surgery within 48 h of admission (89.9–98.4%) was also not maintained after 5 years (91.8%). 30 day mortality improved with continual audit, a trend which continued in 2013. The re-introduction of continuous audit in 2014 demonstrated an improvement in accident and emergency waiting times and time to theatre. Discussion: The Scottish Hip Fracture Audit demonstrated improved standards of care until it was discontinued in 2008. The improvement was not sustained throughout all variables with the 2013 audit. With the re-introduction of regular audit, standards once again improved. We would recommend a more regular audit in an effort to not only improve standards of care for patients with a hip fracture but to maintain them.